2019
DOI: 10.5114/wiitm.2019.85837
|View full text |Cite
|
Sign up to set email alerts
|

Sphenoid sinus septations and their interconnections with parasphenoidal internal carotid artery protuberance: radioanatomical study with literature review.

Abstract: Introduction: Internal carotid artery (ICA) injury is the most dangerous and life-threatening complication in patients operated on due to parasellar tumors via a minimally invasive endoscopic endonasal approach. Sphenoid septal attachment to the ICA protuberance within the sphenoid sinus was found to be one of the anatomical risk factors for ICA injury during transsphenoidal surgery. Aim: To determine the relationship between the sphenoid sinus septa and the parasellar or paraclival internal carotid artery pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 20 publications
1
12
0
Order By: Relevance
“…During ESS, care must be taken not to fracture these septa as this may have catastrophic consequences such as uncontrollable bleeding, retrobulbar hematoma, proptosis and diplopia [ 1 , 25 ]. It has been reported that only one in four IS are located in the midline [ 26 ]. In our study, IS was deviated in 60.4% of individuals: in 30.1%, it was attached onto the ICA protuberance and in 14.3% into the ONC protrusion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During ESS, care must be taken not to fracture these septa as this may have catastrophic consequences such as uncontrollable bleeding, retrobulbar hematoma, proptosis and diplopia [ 1 , 25 ]. It has been reported that only one in four IS are located in the midline [ 26 ]. In our study, IS was deviated in 60.4% of individuals: in 30.1%, it was attached onto the ICA protuberance and in 14.3% into the ONC protrusion.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, IS was deviated in 60.4% of individuals: in 30.1%, it was attached onto the ICA protuberance and in 14.3% into the ONC protrusion. Poirier et al [ 27 ] reported attachment of the IS onto the ICA in 3.4%, Batra et al [ 28 ] in 37.5% and Dziedzic et al [ 26 ] in 49% of cases. In our work, we identified that 30.4% presented AS similar to levels reported by Anusha et al [ 16 ] Jaworek-Troc et al [ 29 ] reported that AS were present in 78.0% of cases, similar to levels reported by Akgül et al [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in up to 10% of cases, the ICA canal courses within 4 mm of the midline [ 6 ]. Insertion of the intersphenoidal septum into the bony ICA canal was anatomically unfavorable in 16.3% of cases, according to Park et al, while, according to Dziedzic et al, 49% of sphenoid sinuses have at least one septum exhibiting involvement with the ICA protuberance [ 19 , 20 ]. During a resection, twisting and pushing movements can cause a bone fragment to injure the ICA wall.…”
Section: Discussionmentioning
confidence: 99%
“…36 Obviously, the rule of thumb is to prevent these injuries by proper training and operator experience, using the "2 surgeons, 4 hands" method, and having a good grasp of patientspecific anatomy utilizing the best preoperative imaging techniques. 30,[37][38][39][40][41][42][43] Anatomical considerations in EES must be kept in the mind to avoid this serious complication. [44][45][46] However, ICA injury may still occur in the best of hands, 47 and apart from exsanguination, this injury may lead to a diverse range of vascular findings such as pseudoaneurysms, arterial spasm, arterial thrombosis/emboli, and caroticocavernous fistula formation.…”
Section: Discussionmentioning
confidence: 99%